In situ diffuse reflectance infrared Fourier-transformed spectroscopy study of solid electrolyte interphase formation from lithium bis(trifluoromethanesulfonyl)imide in 1, 2-dimethoxyethane and 1, 3-dioxolane with and without lithium nitrate additive over lithium and copper metal anodes. (1st June 2022) - Olana, Bikila Nagasa; Lin, Shawn D.; Hwang, Bing-Joe
Abstract: DRIFTS (diffuse reflectance infrared Fourier-transformed spectroscopy) is applied to study the surface reactions over Li foil and Cu foil anodes when using the electrolyte of LiTFSI (LiN(SO2 CF3 )2 ) salt in DME (1, 2-dimethoxyethane) and DOL (1, 3-dioxolane) solvents, with/without LiNO3 (LN) additive. The DRIFTS spectra at open circuit potential (OCV) indicate that DME and DOL are stable, while LiTFSI is chemically decomposed over Li but stable over Cu anode. The absorbance bands suggest that LiSO2 CF3 and Li2 NSO2 CF3 species formed from LiTFSI decomposition over Li. LN is chemically decomposed over both Li and Cu anodes into LiNO2 with Li2 O as the likely accompanying species at OCV. During LSV (linear scan voltammetry) these surface species and also DOL and DME can be electrochemically reduced forming ROLi (CH3 CH2 OCH2 Li/CH3 OCH2 CH2 OLi and CH3 OLi, respectively, from DOL and DME), Li3 N (from TFSI − and LiNO3 ), LiF and Li2 SO2 (from TFSI − ), and Li2 O (from LiNO3 ). Graphical abstract: Image, graphical abstract